Bioremediation and Electricity Generation by Using Open and Closed Sediment Microbial Fuel Cells - Abbas, Syed Zaghum; Rafatullah, Mohd; Khan, Moonis Ali; Siddiqui, Masoom Raza (Frontiers in Microbiology, 2019)
The industrial contamination of marine sediments with mercury, silver and zinc in Penang, Malaysia was studied with bio-remediation coupled with power generation using membrane less open (aerated) and closed (non-aerated) sediment microbial fuel cells (SMFCs). The open and closed SMFCs were showed the maximum voltage generation 300.5 mV (77.75 mW/m2) and 202.7 mV (45.04 (mW/m2), respectively. The cyclic voltammetry showed the oxidation peak in open SMFCs at +1.9 µA and reduction peak at -0.3 µA but in closed SMFCs oxidation and reduction peaks were noted at +1.5 µA and -1.0 µA, respectively. The charge transfer impedance showed that the rates of substrate oxidation and reduction were very low in the closed SMFCs than open SMFCs. The Nyquist arc indicated that O2 act as electron acceptor in the open SMFCs and CO2 in the closed SMFCs. The highest remediation efficiency of toxic metals (Hg (II) ions, Zn (II) ions and Ag (I) ions) in the open SMFCs were 95.03%, 86.69% and 83.65% in closed SMFCs were 69.53%, 66.57% and 65.33%, respectively observed during 60-80 days. The scanning electron microscope and 16S rRNA analysis showed diverse exoelectrogrnic community in the open SMFCs and closed SMFCs. The results demonstrated that open SMFCs could be employed for the power generation and bioremediation of pollutants.